Representaciones Sociales de Cinco Adultos Mayores Frente a su Institucionalizacion en el Geriátrico San Pedro Claver (2014)
This research describes the Social Representations of five elderly institutionalized in the San Pedro Claver Geriatric Home. To conduct the research, the investigators reviewed theelderlie’s testimonies, which where collected using the semi-structured interview technique. The analysis categories includes: beliefs, images and attitudes of these older adults. The results show that the elderly’s belief about institutionalization is negative although they are in that caring home.